A new method for measuring the relative dielectric constant of porous mixed media using GPR, and its application. (24th October 2022) - Ling, Tonghua; He, Wenchao; Zhang, Sheng; Liu, Xianjun; Huang, Fu; Liu, Wenjun
Highlights: The improved TEDAWT method is suitable for signal feature point identification of GPR. A new proposed method has proven more accurate in measuring the relative dielectric constant of materials. The improved TEDAWT method has been shown to improve the accuracy of GPR detection. Abstract: Natural materials mostly consist of porous mixed media, the relative dielectric constant (RDC) of which is a variable. The RDC of measured materials is often simply estimated as a constant value for the purposes of ground-penetrating radar (GPR) detection, which is one of the reasons for the significant quantitative identification error of GPR results. Only by accurately measuring the RDC of porous mixed media to calibrate the electromagnetic wave velocity can accurate quantitative GPR identification results be obtained. However, the difficulty is how precisely to identify the feature points of GPR signal of the measured material. In this study, a model test was carried out in a laboratory setting on porous mixed media consisting of dry sand, dry loam, and limestone. A new method was then proposed to accurately measure the RDC of porous mixed media. On this basis, three stages of accurate measurements of GPR were proposed, namely, signal processing, wavelet analysis, and quantitative identification. Experimental results showed that the relative error rate between the measured value (5.555) and the theoretical value (7.250) of porous mixed media was 23.38%, and the relative error rate of the measured value obtained by the new method was reduced from 13.78% to 1.50% in respect of quantitative recognition of GPR. The proposed method offers both unique advantages in improving the detection accuracy of GPR and great market potential, especially for projects requiring the accuracy of non-destructive testing (NDT). In addition, this study also proposed potential methodological feasibility and research ideas for predicting the physical properties of measured materials by establishing sensitive regions within three-dimensional spaces in the future.